Interaction of obesity and inflammatory bowel disease - Harper, Jason W; Zisman, Timothy L (World journal of gastroenterology : WJG, 2016)
Inflammatory bowel disease(IBD) is a chronic inflammatory condition of unknown etiology that is thought to result from a combination of genetic, immunologic and environmental factors. The incidence of IBD has been increasing in recent decades, especially in developing and developed nations, and this is hypothesized to be in part related to the change in dietary and lifestyle factors associated with modernization. The prevalence of obesity has risen in parallel with the rise in IBD, suggesting a possible shared environmental link between these two conditions. Studies have shown that obesity impacts disease development and response to therapy in patients with IBD and other autoimmune conditions. The observation that adipose tissue produces pro-inflammatory adipokines provides a potential mechanism for the observed epidemiologic links between obesity and IBD, and this has developed into an active area of investigative inquiry. Additionally, emerging evidence highlights a role for the intestinal microbiota in the development of both obesity and IBD, representing another potential mechanistic connection between the two conditions. In this review we discuss the epidemiology of obesity and IBD, possible pathophysiologic links, and the clinical impact of obesity on IBD disease course and implications for management.